An Infantile Low Grade Fibromyxosarcoma Of The Neck: A Rare Case - Rima Zakiyah (Published by Faculty of Medicine Universitas Islam Malang, 2017)
ABSTRACTBackground: Fibrosarcoma is a mesenchymal tumor of adult and pediatric age groups representing 10 to 12% of all soft-tissue sarcomas. Infantile fibrosarcoma is an uncommon tumor of childhood. It represents less than 1% of all childhood cancers but is the most common soft-tissue sarcoma in those under 1 year of age. The tumor may be observed at birth, in infancy or in childhood, and has been called congenital or infantile fibrosarcoma. Fibrosarcoma is one of the types of non-rhabdomyosarcoma soft tissue sarcoma (NRTS) that accounts for 3% of all childhood malignancies. Only 5% of all primary malignant tumors in children arise in the head and neck. The purpose of this paper is to report a rare case of infantile low grade fibromyxosarcomaand the choice of diagnostic radiology modalities.Case: A 2-month-old boy with the rare case of an infantile low-grade fibromyxoid sarcoma (LGFMS). The tumor arose in the paravertebral region of his left posterolateral neck. There is no infiltration to the intracranial or vertebral canal. A review of the literature indicates that this is one of the youngest patients diagnosed with a tumor of this type, and had never been reported as LGFMS. Conclusion: A rare case of infantile low grade fibromyxosarcoma had been reported. Based on the history, physical examination, laboratory examination, and radiologic imaging, the diagnosis of infantile low grade fibromyxosarcoma was established. Magnetic Resonance Imaging (MRI) is the best modality overall for examining soft-tissue masses and is useful in providing information about the local extent, lesion size, and involvement of the neurovascular structures.Keywords:Fibromyxoid, sarcoma, childhood, radiology